Nānā aṇi Mahādajī yāñcī tulanā - Bhānu, Cintāmaṇa Gaṅgādhara (SAMP early 20th-century Indian books project, 1895)
Comparative study of the achievements of Nana Phadnis, 1742-1800 and Madhava Rao Sindhia, Raja of Gwalior, d. 1794.